Influence de l'hydrodynamique des bassins sur la survie et la croissance des larves de turbot (Psetta maxima) - Gaignon, Jean-louis; Petton, Bruno; Quemener, Loic (Conseil Superieur De La Peche, 1998)
During larval rearing phase of turbot, a substantial variability in survival and growth is frequently observed. In this paper, we studied the effects of hydrodynamics in larvae rearing tanks on the survival and the growth of fed and starved larvae, using the following conditions: water flows of 600 and 1200 ml.mn(-1), constant and progressive ones, air flows of 10 and 30 ml.mn(-1), downward and upward water circulation, with direction change during the rearing phase. We also studied the interactions between water circulation direction and feeding conditions by (1) shifting the first feeding day (4 occasions, at 8 hours intervals, from 52 to 76 hours after 95% of hatching) and (2) using 2 amounts of preys (which differ by a factor 3). The results show that water and air flows have a strong effect on the mortality : a 25% water flow increase and a low air flow have negative effects during the mixed feeding period. The water circulation direction influenced strongly the mortality during the whole period :an upward water direction leads to the best survival. These results were confirmed under water circulation direction changes. Under these conditions, the mortality was immediately modified the change from an upward to a downward direction provides high mortalities and conversely. The feeding conditions have no effects on the larvae survival. There is no interactions with water circulation direction on survival. During this rearing phase, nor hydrodynamics conditions, nor the first feeding day shift have an effect on the growth, The amount of preys is the only condition which provides a significant effect on the larval growth. In conclusion, hydrodynamics in rearing tanks has a strong effect on the larvae survival, in order to limit the variability of turbot rearing performances, the control of the air and water flows is of prime importance. The prey availability and their accessibility for the larvae do not seem to be linked with the hydrodynamics effects. Une forte variabilité des performances larvaires est ...